The hip hop movement : from R&B and the civil rights movement to rap and the hip hop generation - Rabaka, Reiland, 1972- (Lexington Books, 2013)
Connecting classic rhythm & blues and rock & roll to the Civil Rights Movement, and classic soul and funk to the Black Power Movement, The Hip Hop Movement critically explores what each of these musics and movements' contributed to rap, neo-soul, hip hop culture, and the broader Hip Hop Movement. Ultimately, The Hip Hop Movement reveals that black popular music and black popular culture have always been more than merely "popular music" and "popular culture" in the con.